Rhodium complexes promoting C O bond formation in reactions with oxygen: The role of superoxo species - Garcia Melchor, Max (My University, 2017)
C−O bond formation in reactions of olefins with oxygen is a long-standing challenge in chemistry for which the very complicated −sometimes controversial− mechanistic panorama slows down the design of catalysts for oxygenations. In this regard, the mechanistic details of the oxidation of the complex [Rh(cod)(Ph2N3)] (1) (cod = 1,5-cyclooctadiene) with oxygen to the unique 2-rhodaoxetane compound [{Rh(OC8H12)(Ph2N3)}2] (2) has been investigated by DFT calculations. The results of this study provide evidences for a novel bimetallic mechanism in which two rhodium atoms redistribute the four electrons involved in the cleavage of the O=O bond. Further, both oxygen atoms are used to create two new C−O bonds in a controlled fashion with 100% atom- economy. The key intermediates that we have found in this process are a mononuclear open-shell triplet superoxo compound, an open-shell singlet ‘μ-(peroxo)’ derivative, and a closed-shell singlet ‘bis(μ- oxo)’ complex. Some of the findings are used to predict the reactions of Rh(I) complexes with oxygen, exemplified by that of the complex [Rh(cod)(OnapyMe2)] (3). Starting from 3, [{Rh(OC8H12)(OnapyMe2)}2] (4) has been prepared and characterized, which represents the second example of a 2-rhodaoxetane compound coming from a oxygenation reaction with oxygen.
PUBLISHED
Keywords: C−O bond formation; Density functional calculations; Dioxygen cleavage; Rhodaoxetanes; Rhodium